Recenzja książki Mariahilf. Geschichte – Theologie – Frömmigkeit, Friedrich Pustet Verlag, hrsg. J. Werz, J. Kreiml, Regensburg 2021, ss. 440 - Wojtczak, Adam (Poznańskie Studia Teologiczne, 2022)
The German title of the book Mariahilf shows that it concerns Mary, in whom Catholics see their Lady of Assistance. Her motherly care and tenderness accompany them in daily lives, especially in times of trials and adversities. In the times of Counter-Reformation the title Auxilium christianorum (Help of Christians) became widespread. The authors of this monograph, as the subtitle clarifies, put it thru historical, theological and cultic analysis. This is not only about the interpretation of its theological significance and cultic application, but also about the discovery of the contexts and planes which helped to propagate it in the German-speaking regions, especially in Austria and Bavaria. In order to achieve this goal the authors of the individual chapters present the way in which this Marian title has become apparent in recent centuries in liturgical piety (the texts of the Mass, antiphons, hymns) as well as popular piety (religious songs, prayers, sermons, shrines). This is to find the answer to what extent the motif of Mary-Lady of Assistance could be present in modern theology and the life of the Church in order to contribute to their revival.